Analytical View of the Use of a Modern Management Method: Talent Management in the Selected Tourism Companies in the Slovak Republic - COCUĽOVÁ, Jana; ĽUBATOMČÍKOVÁ, ĽUBATOMČÍKOVÁ (Journal of Advanced Research in Management; Vol 11 No 2 (2020): JARM Volume XI Issue 2(22) Winter 2020DO - 10.14505//jarm.v11.2(22).01, 2020)
Talent management has recently become a frequently discussed concept among business as and academics alike and one of the priorities of the modern management of all companies, including those operating in the field of tourism. One reason is the fact that due to the similarities caused by globalization, the similarities in social, cultural and economic development, it is increasingly difficult for organizations to gain and maintain a competitive advantage through traditional human resource management practices. Tourism is one of the world's most important industries and also the largest service provider. The most important thing in the tourism business is the right approach to customers. Therefore, the success of the business depends primarily on the quality and skills of employees. The bearers of intellectual capital are key employees with above-average intelligence and better skills, those who actively develop their knowledge, skills and abilities. These employees are the most valuable assets thanks to which the companies that employ them achieve their set goals. The aim of this paper was to evaluate the use of modern management methods, specifically talent management, in selected tourism enterprises in the Slovak Republic and thus provide an analytical view of the use of the talent management in practice. For the research purposes, we collected data through an online questionnaire and then examined the veracity of the two scientific research hypotheses. The aim of the hypotheses was to examine the existence of statistically significant differences in the frequency of use of the talent management with regard to the type of tourism enterprise and the accommodation classification. Inductive statistics methods such as T-test and ANOVA were used during testing.